Analysis Of Employee Performance At UD Bintang Laut - Rahmat Zulkarnain (PT. Inovasi Teknologi Komputer, 2024)
A supplier of frozen fish, UD Bintang Laut is situated in Lenteng, Sumenep. The fresh tuna and other fish obtained from Indonesian ports are used to make the frozen fish products. It is impossible to separate UD Bintang Laut's dedication to offering high-quality fresh fish from each employee's part in organizing, carrying out, and monitoring the quality of high-quality fresh products using a variety of productive and management techniques that are competent, effective, and enforce employee discipline. UD Bintang Laut is indicated to be experiencing problems with the performance of its employees, because this is due to the decline in company production and sales. Direct data collecting was done with the use of research tools in the form of questionnaires. The form of the questionnaire is in the form of written questions, the aim is to obtain information from respondents about what they experience and know in their work environment. The form of questionnaire created as an instrument in this writing is a closed questionnaire because respondents only have to choose the answers that have been provided. In this study, structural equation modeling (SEM) based on variant or component analysis is used for quantitative analysis. The 25 individuals who worked at UD Bintang Laut made up the population used in this study. Since there are fewer than 100 respondents in the population, saturated/census sampling will be the sample method employed in this study. Thus, the author included all 25 responders, or employees, from the UD Bintang Laut population. The research results show that Competence (X1) has a significant positive effect on Employee Performance (Y), Discipline (X2) has a significant positive effect on Employee Performance (Y).